Polysaccharide from Atractylodes macrocephala Koidz. ameliorates DSS-induced colitis in mice by regulating the Th17/Treg cell balance - Yang, Mengjiao; Zhang, Qianwen; Taha, Reham; Abdelmotalab, Mohammed Ismail; Wen, Qing; Yuan, Yuzhu; Zhao, Yongrui; Li, Qingyu; Liao, Chunyu; Huang, Xin; Jiang, Zhenzhou; Chu, Chenghan; et al. (Frontiers in Immunology, 2022)
Atractylodes macrocephala Koidz. is one of the most frequently used traditional Chinese medicines for the treatment of ulcerative colitis (UC). The beneficial effect of polysaccharide from Atractylodes macrocephala Koidz. (PAMK) on UC has been reported, while the underlying mechanism and target remain unclear. In this study, we systematically investigated the therapeutic effect and the underlying mechanism of PAMK in UC based on a mouse model of dextran sodium sulfate (DSS)-induced colitis. PAMK treatment (100 mg/kg, 200 mg/kg and 400 mg/kg) significantly ameliorated DSS-induced colitis, manifested as a reduction in weight loss, disease activity index (DAI), colon shortening, spleen index and histological score. Moreover, PAMK treatment inhibited inflammation and improved the integrity of the intestinal barrier in colitis mice. Mechanistically, microarray analysis determined the critical role of the immunoregulatory effect of PAMK in alleviating UC. Flow cytometry analysis further demonstrated that PAMK treatment regulated the balance between T helper (Th) 17 and regulatory T (Treg) cells in the mesenteric lymph nodes (MLN) and spleen in mice with colitis. In addition, PAMK treatment downregulated the expression of IL-6 and suppressed the phosphorylation of STAT3. Together, these data revealed that PAMK treatment alleviated DSS-induced colitis by regulating the Th17/Treg cell balance, which may be dependent on the inhibition of the IL-6/STAT3 signaling pathway. Our study is the first to elucidate that the underlying mechanism by which PAMK treatment alleviates DSS-induced colitis is associated with an improved the Th17/Treg cell balance. Collectively, the study provides evidence for the potential of PAMK to treat UC.